Impact of insomnia and obstructive sleep apnea on the risk of acute exacerbation of chronic obstructive pulmonary disease. (August 2021) - Li, Shi Qi; Sun, Xian Wen; Zhang, Liu; Ding, Yong Jie; Li, Hong Peng; Yan, Ya Ru; Lin, Ying Ni; Zhou, Jian Ping; Li, Qing Yun
Summary: Chronic obstructive pulmonary disease (COPD) is a major health burden worldwide. Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is characterized by worsening of patients' respiratory symptoms that requires a modification in medication. This event could accelerate disease progression and increase the risk of hospital admissions and mortality. Both insomnia and obstructive sleep apnea (OSA) are prevalent in patients with COPD, and are linked to increased susceptibility to AECOPD. Improper treatment of insomnia may increase the risk of adverse respiratory outcomes for patients with COPD, while effective continuous positive airway pressure (CPAP) treatment may reduce the risk of AECOPD and mortality in patients with overlap syndrome. Sleep disorders should be considered in clinical management for COPD.